“Bright–English for Beginners” Application as a Learning Media: Taking EFL Teachers’ Perspective: “Bright–English for Beginners” sebagai Media Pembelajaran: Perspektif Guru Bahasa Inggris sebagai Bahasa Asing (EFL) - Zahira Shofa Sihotang; Diah Safithri Armin (Academia Open, 2025)
General Background: Mobile-Assisted Language Learning (MALL) has become a transformative tool in English language instruction, especially at the elementary level. Specific Background: The "Bright–English for Beginners" application is among the innovative platforms aiming to enhance early EFL learning through interactive, gamified, and adaptive content. Knowledge Gap: While existing literature emphasizes student outcomes, limited research addresses teachers’ perspectives and the practical challenges of implementing such technology in classrooms. Aims: This study explores elementary EFL teachers’ experiences using the Bright application, focusing on perceived benefits, pedagogical challenges, and instructional strategies. Results: Teachers reported increased student motivation, personalized learning, and improved engagement through multimedia features and assessment tools. However, challenges included unstable internet, curriculum misalignment, limited training, and skepticism from stakeholders. Novelty: Unlike prior studies, this research foregrounds the teacher’s role in MALL integration and highlights creative pedagogical adaptations—peer learning, digital portfolios, and real-world language tasks—as critical to successful implementation. Implications: Findings suggest that effective educational technology adoption requires not just functional tools, but robust infrastructure, curriculum integration, and ongoing professional development. This study contributes practical insights for developers, educators, and policymakers aiming to enhance early language learning through digital platforms.Highlight : Teachers believe that this application significantly improves student motivation and participation. The main challenges include unstable internet connections and curriculum compatibility. Creative strategies such as peer learning and contextual assignments reinforce the effectiveness of the application. Keywords : Bright–English for Beginners, Mobile Application, EFL Teachers, English Language Learning, Teacher Perspective